HUBUNGAN KARAKTERISTIK DAN MOTIVASI IBU DENGAN EFEKTIFITAS ASI EKSKLUSIF DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA TAHUN 2019 - Fitriana Ritonga (Jurnal Ilmiah Kebidanan Imelda, 2021)
Mother's Milk (ASI) is the only type of food that meets all the elements of a baby's physical, psychological, social and spiritual needs. Breast milk contains nutrients, hormones, insecurity, anti-allergy, and anti-inflammatory. Nutrients in breast milk include nearly 200 nutrients (Puspitasari, 2016). Exclusive breast milk is a baby who is only given breast milk, without the addition of other fluids such as formula milk, oranges, honey, tea water, water, and without the addition of solid foods such as bananas, papaya, milk porridge, biscuits, rice porridge, and team (Roesli, 2005). This research is a quantitative research using Correlative Descriptive design with an intermittent cross sectional approach. With a sample of respondents are mothers who have children aged 6 - 24 months, the sampling technique of this study is Accidental Sampling. Bivariate analysis used is Chi-square statistic. From the bivariate results there is no relationship between maternal age and the effectiveness of breastfeeding, there is no relationship between maternal age and the effectiveness of breastfeeding, there is a relationship between education and the effectiveness of breastfeeding, there is no relationship between education and the effectiveness of breastfeeding, there is a relationship between knowledge and the effectiveness of breastfeeding, there is no the relationship between parity with the effectiveness of breastfeeding. Suggestions from researchers For health workers to improve the quality of related health services continue to be improved, for mothers and families it is hoped that they can add information to families and the importance of researchers increasing the effectiveness of exclusive breastfeeding to increase infant life expectancy through exclusive breastfeeding, to increase knowledge about health, especially in health.